Does Infant Feeding Method Impact on Maternal Mental Health? - Xu, F.; Li, Z.; Binns, Colin; Bonello, M.; Austin, M.; Sullivan, E. (Mary Ann Liebert, Inc. Publishers, 2014)
Background: Breastfeeding has been reported to reduce the risk of postpartum anxiety and depression. However, little is known of the effects of breastfeeding on hospital admissions for postpartum mental disorders. Materials and Methods: This is a population-based longitudinal cohort study using linked data. All mothers who gave birth to a live infant between 2007 and 2008 in New South Wales, Australia were followed up for 1 year for hospital admissions with diagnoses of psychiatric and/or substance use disorders. Results: There were 186,452 women who were reported as giving birth in New South Wales between 2007 and 2008. The ‘‘any breastfeeding’’ rate at the time of discharge was 87.1%. In total, 2,940 mothers were admitted to the hospital with psychiatric diagnoses within 12 months of birth. The first hospital admission for the diagnoses of overall mental illness was 32 days earlier for non-breastfeeding mothers compared with those with full breastfeeding. Mothers who did not breastfeed were more likely to be admitted to the hospital in the first year postpartum for schizophrenia (adjusted relative risk [ARR] = 2.0; 95% confidence interval [CI] 1.3, 3.1), bipolar affective disorders (ARR = 1.9; 95% CI 1.1, 3.5), and mental illness due to substance use (ARR = 1.8; 95% CI 1.3, 2.5) compared with full breastfeeding mothers. Conclusions: Breastfeeding is associated with a decrease in the risk of subsequent maternal hospital admissions for schizophrenia, bipolar affective disorders, and mental illness due to substance use, in the first postpartum year.